Anti-reflection sub-wavelength structures design for InGaN-based solar cells performed by the finite-difference-time-domain (FDTD) simulation method. (April 2015) - Yang, L.M.; Pan, C.Y.; Lu, F.P.; Chang, C.W.; Feng, S.W.; Tu, L.W.
Abstract: The design of wide-spectrum anti-reflection (AR) sub-wavelength structures (SWS) for InGaN-based solar cells is investigated in this study. The design parameters such as base diameter and height of the SWS, as well as the pitch and fill factor of the SWS array are studied numerically in this research. The simulation is carried out by the finite-difference-time-domain (FDTD) analysis. We found that the simultaneous increase of the height of the SWS and the fill factor of the SWS array can effectively suppress the rising of the reflectance in the near-infrared range (1–2 μm). The results of the reflectance vs. wavelength for SWS array are also compared with that of the double layer anti-reflection (DLAR) coating. In addition, the effective reflectance R eff which is based on AM 1.5G 1 sun considerations for various conditions is listed inTable 1 for comparison. It shows that as the height equals to 500 nm and the fill factor is greater than 0.83 ( R eff =1.4%), or the fill factor equals to 1.0 and the height is greater than 200 nm ( R eff =1.7%), the effective reflectance of SWS array is lower than that of DLAR coating ( R eff =2.6%). Highlights: The height and fill factor are two key factors of the optimum AR SWS design. Raising the height will reduce the Fresnel׳s reflection on SW cone surface. Increasing fill factor can help to trap scattered light. Raising height and fill factor simultaneously can effectively lower the reflectance.